Expression of HGF, MMP-9 and TGF-β1 in the CSF and cerebral tissue of adult rats with hydrocephalus. (19th April 2013) - Zhang, Shaolin; Chen, Donghan; Huang, Caiquan; Bao, Jianfeng; Wang, Zhanxiang
<x xml:space="preserve">Abstract</x> Object: The hepatocyte growth factor (HGF), matrix metallopeptidase-9 (MMP-9) and transforming growth factor-β1 (TGF-β1) are important cytokines with modulatory actions in the nervous system. In this study, we attempted to investigate the role and expression of HGF, MMP-9 and TGF-β1 in the cerebral tissue and cerebrospinal fluid (CSF) of adult rats with hydrocephalus induced via intraventricular kaolin injection. Methods: Adult male Sprague-Dawley rats were randomly divided into two groups: control group (n = 12) and experimental group (n = 20). Kaolin was injected into the lateral ventricle of experimental animals. Control rats underwent the same procedure but received sterile saline injection instead of kaolin. Magnetic resonance imaging was used to assess ventricle size. The CSF was studied by enzyme-linked immunosorbent assay and the excised brains were studied by reverse-transcription polymerase chain reaction and immunohistochemical analyses to measure the messenger RNA and protein expression level of HGF, MMP-9 and TGF-β1. Results: Hydrocephalus was induced in all the rats after kaolin injection into the lateral ventricle. After 2 weeks, the expressions of HGF, MMP-9 and TGF-β1 in the CSF and cerebral tissue were significantly increased in the experimental group compared with the control group. Conclusions: This results indicated that HGF, MMP-9 and TGF-β1 may participate in the formation and prognosis of hydrocephalus after kaolin induction.